Misexpression of a transcriptional repressor candidate provides a molecular mechanism for the suppression of awns by Tipped 1 in wheat - Würschum, Tobias (Journal of experimental botany, 2020)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology.